CJ CheilJedang: a South Korean conglomerate promoting much more than k-style (2022)
Since the end of the 20th century, South Korea has succeeded in exporting cultural products that have attracted worldwide attention. This phenomenon has been an opportunity to make certain features of Korean culture internationally known and to build a positive image of the country abroad, which gives it advantages in global competition by associating its companies and products with values compatible with those of Western and Asian consumers. Among the most important Korean conglomerates in this line of business is the CJ Group, which was born from the separation of Samsung in the 1990s and whose companies are leaders in the cultural, media and entertainment industries. Thanks to K-style and a powerful international marketing strategy, CJ E&M has become one of the most recognized companies of the CJ Group, capable of influencing the aesthetic and cosmopolitan definition of certain lifestyles associated with the consumption of high-tech goods, cosmetics, and healthy products. The aim of this article is to present a case that shows how the expansion of a Korean conglomerate included the cultural industry among its business areas, with which it has spread worldwide and triggered spillover effects into other industries. The focus will be on the agency of conglomerates and their leaders as drivers of the internationalization of Korean culture, in particular the trajectory of CJ CheilJedang and how the four divisions within it leveraged their capabilities to create synergies that produce attractive brands and images in the international marketplace. The central argument is that the “Korean wave” owes its strength to the characteristics of Korea’s corporate system, which is, in turn, a result of Korea’s developmentalist political economy.